Navigating Outward Bound: a first-person exploration of situational exposure through an autistic lens - Newcombe N; Good GA (Springer Nature on behalf of Outdoor Education Australia, 2025)
This article explores the first author’s experience as an autistic woman attending a five-day Professional Leadership course at Outward Bound in Aotearoa, New Zealand. Through a first-person autoethnographic narrative, Nicolina shares why she chose Outward Bound and how she navigated the challenges of situational exposure in a physically and socially demanding outdoor education program, using accommodations to maximise time in the learning zone. She discusses the sensory sensitivities and need for routines that often accompany Autism Spectrum Disorder and demonstrates how she adapted and advocated for her needs while participating in a mainstream course. The barriers she encountered and the positive outcomes she achieved are described. Four themes emerged, these were motivation, challenges, coping and thriving through adaptations, and hope. By reflecting on the balance between growth and anxiety within the comfort zone model, this article offers insights for autistic people, outdoor educationalists, and practitioners. Recommendations call for increased awareness and flexibility in accommodating neurodivergent people in adventure education contexts.
Keywords: Autism spectrum disorder; Comfort zone; Outdoor education; Situational exposure